Sulphur vulcanization of NR latex: reducing chemical residues in NR latex products part 1 / Asiah Abdullah … [et al.] - Abdullah, Asiah; Md. Yatim, Amir Hashim; Samsuri, Azemi; Md. Som, Fauzi (2004)
The process of vulcanization requires chemicals such as crosslinkers, accelerators, activators and anti-oxidants. The unused chemicals during the vulcanization process may be left as residues in the final latex products. This brought about the concern of chemical residues eluting from the products while in service which can cause allergy Type IV in certain individuals. The residual thiocarbamate accelerator in the latex films was quantified using HPLC method. Results of the study indicated that the crosslink concentration and vulcanization time influenced the amount of extracted residual ZDEC. The study of the fractured surface of tensile test piece by SEM technique showed that the appearance of the surface could be correlated with the physical properties of the latex films in particular to the crosslink values. Sulphur probe experiment results showed a sulphur donor system yielded higher mono and di sulphidic crosslink than the elemental sulphur system.